PENERAPAN LANGKAH POLYA DALAM MENENTUKAN JARAK ANTARA DUA GARIS LURUS G1 DAN G2 - Radiatul Adawiah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
The purpose of this research is to describe the implementation of Polya phase that can improve student learning outcomes in solving word problems a matter of geometry about determine the distance between two straight lines g1 and g2 Semester IV Mathematics Education Study Program STKIP Paris Barantai Kotabaru. This type of research is a classroom action Data collection techniques that were presented in this study. Based on the result of the research learning to use Polya phase can increase the student’s learning outcomes to solving the word problem about determine the distance between two straight lines g1 and g2 Semester IV Mathematics Education Study Program STKIP Paris Barantai Kotabaru, those are: 1) understanding the proble; 2) devising plan, 3) carrying out the plan;and 4) looking back at a complete solution. Key words : Polya Phase; Learning Outcomes; Word Problem; Distance of two lines.